2018
DOI: 10.1093/jxb/ery368
|View full text |Cite
|
Sign up to set email alerts
|

CO2 modulation of the rates of photosynthesis and light-dependent O2 consumption inTrichodesmium

Abstract: The ratio of light-driven O2 consumption to gross photosynthetic O2 evolution decreased significantly with increasing CO2, which is probably due to a reduced cost of operating the carbon-concentrating mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 54 publications
2
11
0
Order By: Relevance
“…The data groupings consisted of: (a) combined low/mid CO 2 , (b) combined low/high CO 2 , (c) combined mid/ high CO 2 and (d) all CO 2 data combined. Note, as previous studies have shown that Trichodesmium's maximum growth rate (µ max ) is significantly reduced at low CO 2 relative to mid CO 2 , and is consistently ~10% higher from mid to high CO 2 (Boatman, Davey, Lawson, & Geider, 2018;Boatman et al, 2017;Boatman, Mangan, Lawson, & Geider, 2018;Boatman, Oxborough, et al, 2018), ′ max was maintained independent between CO 2 conditions. Having processed all model iterations by optimizing all parameter groupings, maximum likelihood (L) values were calculated using each model's residual sum of squares and the number of data points (n = 184).…”
Section: Parameter Optimizationsupporting
confidence: 56%
“…The data groupings consisted of: (a) combined low/mid CO 2 , (b) combined low/high CO 2 , (c) combined mid/ high CO 2 and (d) all CO 2 data combined. Note, as previous studies have shown that Trichodesmium's maximum growth rate (µ max ) is significantly reduced at low CO 2 relative to mid CO 2 , and is consistently ~10% higher from mid to high CO 2 (Boatman, Davey, Lawson, & Geider, 2018;Boatman et al, 2017;Boatman, Mangan, Lawson, & Geider, 2018;Boatman, Oxborough, et al, 2018), ′ max was maintained independent between CO 2 conditions. Having processed all model iterations by optimizing all parameter groupings, maximum likelihood (L) values were calculated using each model's residual sum of squares and the number of data points (n = 184).…”
Section: Parameter Optimizationsupporting
confidence: 56%
“…For Trichodesmium and Dolichospermum, only a PQ below 1 (0.8; Fig. 3) could explain the ratio of measured O 2 and pH gradients, in agreement with previous reports of PQ values for Trichodesmium (e.g., PQ 0.45-0.61, Carpenter and Roenneberg 1995; PQ 1.0, Boatman et al 2019). The slight underestimation of pH deviations by the model even at these low PQ levels (Fig.…”
Section: Microenvironment Carbonate Chemistry Under Present-day Conditionssupporting
confidence: 91%
“…The involvement of Flavodiiron proteins (Flvs) in light-dependent O 2 uptake was further established in cyanobacteria (Helman et al, 2003;Allahverdiyeva et al, 2013), and more recently in microalgae (Chaux et al, 2017). MIMS is nowadays widely used to understand the fate of the photosynthetic electron flow in various environmental conditions and mutant of cyanobacteria (Ermakova et al, 2016;Boatman et al, 2018;Luimstra et al, 2019), microalgae (Fisher and Halsey, 2016), or coral reef symbiosis (Einbinder et al, 2016).…”
Section: Assessment Of Photosynthetic Oxygen Exchangementioning
confidence: 99%